Flavivirus susceptibility in Aedes aegypti - Black, William C.; Bennett, Kristine E.; Gorrochótegui Escalante, Norma; Barillas Mury, Carolina V.; Fernández Salas, Ildefonso; Muñoz, María de Lourdes; Farfán Ale, José Arturo; Olson, Ken E.; Beaty, Barry J. (2002)
Aedes aegypti is the primary vector of yellow fever (YF) and dengue fever (DF) flaviviruses worldwide. In this review we focus on past and present research on genetic components and environmental factors in Aedes aegypti that appear to control flavivirus transmission. We review genetic relationships among Ae. Aegypti populations throughout the world and discuss how variation in vector competence is correlated with overall genetic difference among populations. We describe current research into how genetic and environmental factors jointly affect distribution of vector competence in natural populations. Based on this information, we propose a population genetic model for vector competence and discuss our recent progress in testing this model. We end with a discussion of approaches being taken to identify the genes that may control flavivirus susceptibility in Ae. Aegypti.